Characterization of and isolation methods for plant leaf nanovesicles and small extracellular vesicles - Liu, Yuan; Wu, Sherry; Koo, Yeonjong; Yang, An; Dai, Yanwan; Khant, Htet; Osman, Samantha R; Chowdhury, Mamur; Wei, Haichao; Li, Yang; Court, Karem; Hwang, Elaine; et al. (Nanomedicine, 2020)
Mammalian small extracellular vesicles (sEVs) can deliver diverse molecules to target cells. However, they are difficult to obtain in large quantities and can activate host immune responses. Plant-derived vesicles may help to overcome these challenges. We optimized isolation methods for two types of plant vesicles, nanovesicles from disrupted leaf and sEVs from the extracellular apoplastic space of Arabidopsis thaliana. Both preparations yielded intact vesicles of uniform size, and a mean membrane charge of approximately −25 mV. We also demonstrated applicability of these preparative methods using Brassicaceae vegetables. Proteomic analysis of a subset of vesicles with a density of 1.1-1.19 g mL−1 sheds light on the likely cellular origin and complexity of the vesicles. Both leaf nanovesicles and sEVs were taken up by cancer cells, with sEVs showing an approximately three-fold higher efficiency compared to leaf nanovesicles. These results support the potential of plant-derived vesicles as vehicles for therapeutic delivery. Plants provide an inexpensive and rich source of vesicles with future therapeutic delivery potential. Methodologies are presented for isolating nanovesicles from blended whole plant leaves and small extracellular vesicles from the apoplast, the plant leaf extracellular fluid. These methods yield large quantities of intact vesicles with uniform size. Both vesicle species are readily taken up by cancer cells, with a 3-fold higher uptake of the apoplast-enriched small extracellular vesicles (sEVs) compared with the leaf nanovesicles. We further demonstrated applicability of our methodology with commonly consumed vegetables of the Brassicaceae family. This work may pave the way for further testing of plant-derived nanovesicles and sEVs as vehicles for therapeutic delivery. [Display omitted]